STUDI STRATEGI PERENCANAAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDN KALONGAN 01 - Muji, Sri; Chory Praseptiana; Nurul Apriliya; Ngurah Ayu Nyoman Murniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze planning strategies and identify supporting and inhibiting factors in the implementation implemented to improve the quality of education at SDN Kalongan 01. This research uses a qualitative case study approach with the aim of understanding in depth the planning strategies implemented by SDN Kalongan 01 in improving the quality of education . The planning strategy implemented at SD Negeri Kalongan 01 has had a positive impact on the quality of education. However, there are still several challenges that need to be overcome.